A Monocentric Cohort of Obstetric Seronegative Anti-Phospholipid Syndrome - Truglia, Simona; Capozzi, Antonella; Mancuso, Silvia; Recalchi, Serena; Spinelli, Francesca Romana; Perricone, Carlo; De Carolis, Caterina; Manganelli, Valeria; Riitano, Gloria; Garofalo, Tina; Longo, Agostina; De Carolis, Sara; et al. (Frontiers in Immunology, 2018)
The present study was conducted to diagnose obstetric antiphospholipid syndrome (OAPS) in patients with clinical signs suggestive of antiphospholipid syndrome (APS), but persistently negative for conventional anti-phospholipid antibodies (aPL). Sera from 61 obstetrical seronegative APS (SN-APS) patients were analysed for anti-cardiolipin antibodies (aCL) using TLC-immunostaining, for anti-cardiolipin/vimentin antibodies (aCL/Vim), anti-phosphatidylserine/prothrombin antibodies (aPS/PT), IgA anti-β2glycoprotein I antibodies (aβ2GPI) and IgA aCL antibodies by enzyme-linked immunosorbent assay (ELISA). Taken together, our findings show that in 50 out of 61 SN-APS (81.9%) at least one aPL/cofactor antibody was detected using the assays under test. Results revealed that 76% of SN-APS patients resulted positive for aCL by TLC-immunostaining, 54% for aCL/Vim, 12% for aPS/PT, 4% for IgA aβ2GPI and 2% for IgA aCL. Thirty-five out of 61 patients were followed up and the tests were repeated on two occasions, at least 12 weeks apart. Twenty-six out of 35 SN-APS (74.3%) were positive at least one non-conventional test; only 2 patients (5.7%) did not confirm the positivity to the second test. These findings suggest that non-conventional test, mainly aCL/Vim and aCL detected by TLC-immunostaining seem to be the most sensitive approaches for finding out aPL in patients with obstetric SN-APS. Since a diagnosis of APS is required to direct physicians to treatments that significantly improve the birth rate, this work has important therapeutic and prognostic implications.